Otolith morphology and body size relationships of Nemipterus japonicus (Bloch, 1791) in the northern Oman Sea - Seyfabadi, J.; Afshari, M.; Valinassab, T. (Indian Journal of Fisheries, 2014)
Otolith morphology of the Japanese threadfin bream, Nemipterus japonicus (Family Nemipteridae) and its relationships to fish size was examined. Samples were collected from Chabahar area (the northern Oman Sea). Otolith descriptions were based on its outline, including otolith length (OL, mm), height (OH, mm), weight (OW, g) as well as perimeter (OP, mm), and sulcus acusticus features. Paired t-test showed no significant difference between left and right otolith dimensions. Regression models relating each otolith morphometric parameters to fish length and weight revealed the best one between otolith weight with fork length, body weight and otolith perimeter.